Two-timescale unlicensed spectrum partitioning algorithm between LTE and Wi-Fi network - Weihua WU; Runzi LIU; Qinghai YANG (Tongxin xuebao)
According to the spectrum partitioning decisions of Wi-Fi and LTE respectively depended on global channel state information (CSI) and local CSI, an online two-timescale iteration algorithm was developed.The Wi-Fi spectrum was partitioned at the large timescale according to the global CSI whereas the LTE spectrum was partitioned according to the fast-changing local CSI.Then, the adaptive compensation mechanism was designed for improving the tracking performance of the two-timescale algorithm.Moreover, the sufficient condition was derived for the two-timescale algorithm tracking the moving equilibrium point without errors.Finally, the simulation results show that the proposed two-timescale algorithm achieves excellent system performance at very low overhead.